Intermediate Role of Presenteeism in Relationship Between Organizational Stress and Organizational Silence - Ersen, Nadir; Usta, Ugur Can; Bayram, Bahadir Cagri; Akyüz, Ilker (Faculty of Forestry, University of Zagreb, 2023)
The purpose of this study is to investigate the mediating role of presenteeism in the relationship between organizational stress and organizational silence of 305 forest products employees in İstanbul and Kocaeli, Turkey. According to our literature review, although some important studies about presenteeism, stress, and silence can be found, this study is the first to explore the mediating role of presenteeism in the relationship between organizational stress and organizational silence in forest products sector. The research was designed as a field study and conducted using a questionnaire. The questionnaire involved forest industry employees’ demographic data, Organizational Stress Scale, Organizational Silence Scale, and Stanford Presenteeism Scale. Data were analyzed in SPSS and AMOS, incorporating statistical tests such as exploratory and confirmatory factor analysis, correlation analysis, and structural equation modeling. Results of the analyzed data showed that presenteeism had a significant moderating effect on the relationship between organizational stress and organizational silence. Moreover, organizational stress had a positive effect on presenteeism, while organizational silence had a negative effect. Organizational stress had no effect on organizational silence. Therefore, managers should develop strategies for coping with stress to reduce presenteeism behavior of their employees and identify organizational stress factors causing organizational silence.
Keywords: drvoprerađivački sektor; Forestry; SD1-669.5; prezentizam; forest products sector; stres; stress; šutnja; silence; presenteeism; 2. Zero hunger; 9. Industry and infrastructure; 15. Life on land; 12. Responsible consumption; 5. Gender equality; 10. No inequality